BUNDA MENYAPA CAMPAIGN: INITIATING INSTITUTIONAL ADVOCACY FOR EARLY CHILDHOOD EDUCATION THROUGH PUBLIC DISCUSSION IN KEDUNGBANTENG, BANYUMAS - Iwan Kurniawan; Muthmainah Muthmainah; Tatik Ariyati (Jurnal Pengabdian Indonesia (JPI), 2026)
The Bunda Menyapa Campaign is a community service initiative designed to initiate institutional advocacy for early childhood education through the involvement of Bunda PAUD at the village and sub-district levels. This activity was conducted in the form of a public discussion involving the Bunda Menyapa PKM project team, Bunda PAUD Desa Kedungbanteng Kecamatan Kedungbanteng, Banyumas District, and college students from the Early Childhood Education Teacher Education Study Program of Universitas Muhammadiyah Purwokerto. The students participated as the proposing group of the campaign idea and as the writers of the Bunda Menyapa campaign song. The activity aimed to formulate the initial embryo of the Bunda Menyapa Campaign as an institutional advocacy model to be proposed to Bunda PAUD Kabupaten Banyumas. The method consisted of participatory public discussion, campaign concept presentation, stakeholder dialogue, theme-song discussion, and initial review of a policy brief proposal. The result of the activity was the formation of an early campaign concept that integrates symbolic leadership, community communication, institutional advocacy, and policy recommendation. The discussion also opened an opportunity for the policy brief proposal to be developed into a practical advocacy document for strengthening PAUD governance in Banyumas District.